Biologically Emulated Flexible Sensors With High Sensitivity and Low Hysteresis: Toward Electronic Skin to a Sense of Touch. Issue 32 (14th July 2022) - Guo, Xiaohui; Zhou, Deyi; Hong, Weiqiang; Wang, Dandan; Liu, Tianqi; Wang, Di; Liu, Long; Yu, Shencheng; Song, Yanjun; Bai, Su; Li, Yewei; Hong, Qi; et al.
Abstract: Recently, flexible pressure sensors (FPSs) have attracted intensive attention owing to their ability to mimic and function as electronic skin. Some sensors are exploited with a biological structure dielectric layer for high sensitivity and detection. However, traditional sensors with bionic structures usually suffer from a limited range for high‐pressure scenes due to their high sensitivity and high hysteresis in the medium pressure range. Here, a reconfigurable flea bionic structure FPS based on 3D printing technology, which can meet the needs of different scenes via tailoring of the dedicated structural parameters, is proposed. FPS exhibits high sensitivity (1.005 kPa −1 in 0–1 kPa), wide detection range (200 kPa), high repeatability (6000 cycles in 10 kPa), low hysteresis (1.3%), fast response time (40 ms), and very low detection limit (0.5 Pa). Aiming at practical application implementation, FPS has been correspondingly placed on a finger, elbow, arm, neck, cheek, and manipulators to detect the actions of various body parts, suggestive of excellent applicability. It is also integrated to make a flexible 3 × 3 sensor array for detecting spatial pressure distribution. The results indicate that FPS exhibits a significant application potential in advanced biological wearable technologies, such as human motion monitoring. Abstract : This study introduces a reconfigurable flea bionic structure flexible pressure sensor based on 3D printing technology, which can meet the needs of different scenes via tailoring of the dedicated structural parameters. The proposed device exhibits excellent performance experimentally, which indicates that it exhibits a significant application potential in advanced biological wearable technologies, such as human motion monitoring.